CALL and Professionalisation: Short Papers From EUROCALL 2021 2021
DOI: 10.14705/rpnet.2021.54.1313
|View full text |Cite
|
Sign up to set email alerts
|

Machine translation literacy: a panorama of practices at Swiss universities and implications for language teaching

Abstract: This short paper presents the quantitative results of an online survey of Swiss university students and staff on their use of Machine Translation (MT). The analysis of the 3,713 responses throws light on the context, purposes, degree of successive revisions, and ethical considerations surrounding the use of MT. With regards to language teachers and students, the quantitative data allows us to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…MT literacy is also referred to for the first time, due to the increasing research outputs on the topic and the associated societal impact of MT usage (e.g. Bowker and Ciro 2019;Delorme Benites et al 2021;Kenny 2022;Krüger and Hackenbuchner 2022).…”
Section: Pe Trainingmentioning
confidence: 99%
“…MT literacy is also referred to for the first time, due to the increasing research outputs on the topic and the associated societal impact of MT usage (e.g. Bowker and Ciro 2019;Delorme Benites et al 2021;Kenny 2022;Krüger and Hackenbuchner 2022).…”
Section: Pe Trainingmentioning
confidence: 99%
“…Language learners' frequent and extensive use of machine translation (MT) has been shown in several survey studies indicating MT is used in many aspects of language learning, both in and outside of class (Briggs, 2018;Clifford et al, 2013;Jolley & Maimone, 2015;). Recent studies find that on average more than 90% of language students use MT, and more than half of them use them regularly (more than once a week) (Delorme Benites et al, 2021;Kok Wei, 2021). Studies also document the students' recognition of practical benefits of MT, including fast and free access (Garcia & Pena, 2011), quick correction of spelling and grammar errors (Ducar & Schocket, 2018) and capability of multimodal inputs (Niño, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies investigating the accuracy of MT outputs found differences in terms of translation units (e.g., word or phrase vs sentence or paragraph), MT types, text types and language pair (Lee, 2021). Although students seem to be generally satisfied with the accuracy of MT outputs (Delorme Benites et al, 2021;Kok Wei, 2021), studies indicate that how students use MT outputs is significantly correlated with learners' proficiency levels. Higher-proficiency learners seem to be more successful in detecting and correcting errors in MT outputs and using MT outputs to revise their L2 writing (Chung, 2020;Lee & Briggs, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations